Patterns of Using Complementary and Alternative Medicine by Stroke Patients at Two University Hospitals in Korea. Issue 2 (2008) - Shin, Yong-Il; Yang, Chung-Yong; Joo, Min-Cheol; Lee, Sam-Gyu; Kim, Jae-Hyung; Lee, Myeong Soo
Abstract : This study measured the prevalence of complementary and alternative medicine (CAM) use among Korean stroke patients. Questionnaire-based 20-min interviews were conducted at the hospitals by a trained nurse after an outpatient visit. It included questions on demographic information, clinical information and the utilization of CAM. Of 304 stroke-patient respondents, 164 (54%) had used CAM, of which 66% had started taking CAM products following suggestions from family members and other relatives. Of the 57% of users who felt that CAM was effective, 84% considered that it improved the symptoms of stroke and 16% felt it was effective in achieving psychological relaxation. Of the eight CAM categories used by respondents, 92% used traditional Oriental medical treatments, 36% used plant- and animal-derived over-the-counter health care products, 24% used minerals and vitamins, and 11% used manual therapies. The majority of stroke patients (68%) were trying a new type of CAM, and half of the respondents (45%) relied on the knowledge of their general practitioner about CAMs when deciding whether to use them. Most of the stroke patients in this study used CAM, and a half of them reported beneficial effects. Despite the presence of adverse side effects, they tended to be used without discussion with chief physicians, and hence physicians should be actively involved in the usage of CAM.